DIAGNOSTIC ACCURACIES OF DYNAMIC ULTRASOUND AND MRI FOR ANTERIOR CRUCIATE LIGAMENT (ACL) TEAR, TAKING ARTHROSCOPY AS GOLD STANDARD (Journal of Medical & Health Sciences Review, 2025)
OBJECTIVE: To determine the diagnostic accuracy of MRI and ultrasound in detecting anterior cruciate ligament tears, keeping arthroscopy as gold standard.MATERIALS AND METHODS: A cross-sectional study was done at Radiology Department, Lahore, General Hospital, Lahore. Duration of the study was six months after the approval of synopsis. A sample size of 73 cases was calculated using 95% confidence interval, expected prevalence of ACC as 48.5% (8) and expected sensitivity and specificity as 88% and 82% (8) and 13% as margin of error. Non-Probability consecutive sampling technique was used. Inclusion criteria included patients with suspected ACL tear undergoing arthroscopy at department of orthopedics and trauma at Lahore General Hospital. Data analysis was done using SPSS 22 version. Data was stratified age, gender, BMI and duration of symptoms. Chi-Square test was used post-stratification.P-Value of equal or less than 0.05 was considered significant.RESULTS: The study assessed the effectiveness of MRI and ultrasonography (USG) in diagnosing ACL tears, comparing their accuracy to arthroscopy. The demographic analysis showed that the majority of participants were male, with an average age of 32.5 years and a mean BMI of 25.7 kg/m².MRI demonstrated higher diagnostic accuracy than USG, with sensitivity and specificity values of 94.2% and 89.7%, respectively. USG, while less precise, still provided reasonable sensitivity (85.3%) and specificity (78.6%). The comparison of findings showed MRI had more true positives and fewer false negatives compared to USG, reinforcing its reliability.Statistical analysis confirmed a significant association between MRI and arthroscopic findings (p = 0.003), while USG also showed a significant, but slightly weaker, association (p = 0.012).CONCLUSION: The study highlights that MRI remains the superior imaging modality for diagnosing ACL tears, showing higher sensitivity, specificity, and accuracy compared to ultrasonography. However, USG remains a viable alternative in settings where MRI is unavailable.